Income Increase and Moving to a Better Neighbourhood: An Enquiry into Ethnic Differences in Finland - Maria Vaalavuo; Maarten van Ham; Timo M. Kauppinen (Institute of Labor Economics (IZA), 2017)
Concentration to disadvantaged neighbourhoods may hinder immigrants' opportunities for social integration, so equal chances of translating available economic resources into mobility to less disadvantaged neighbourhoods are important. This paper adds to existing research on exits from poor neighbourhoods by focusing on the effects of income increase on residential mobility. We analyse intra-urban residential mobility from low-income neighbourhoods into non-low-income neighbourhoods among immigrants and native-born residents in three urban regions in Finland. We use longitudinal register data for the 2004–2014 period for the full Finnish population, allowing a dynamic analysis of changes in income and neighbourhood of residence. Based on multinomial logit modelling of migration outcomes, we found that an increase in income is associated with moving both to low-income and non-low-income areas even when controlling for initial income level. Upward income mobility was connected to exit from low-income areas in a quite similar way among immigrants and native-born Finns. The findings suggest that policies e.g. improving the labour market opportunities of immigrants are effective in reduction of residential segregation. However, we were not able to completely explain the differences between native-born Finns and immigrants in moving patterns. The differences between the cities were opposite for immigrants and native-born Finns, corresponding to differences in immigration history and levels of ethnic segregation. Therefore, the local context matters for spatial integration outcomes.
Keywords: O15; O18; P25; R23; 330; immigration; segregation; housing; residential mobility; income mobility; register data; Finland